Factors to Increase Tourist Loyalty in North Sumatera - Onan Marakali Siregar; Selwendri Selwendri; Maulidina Maulidina (Budapest International Research and Critics University, 2020)
North Sumatra Province is an area that has several attractions, both natural and cultural attractions. Some well-known tourist objects from abroad to foreign countries such as Lake Toba, and Mount Lawang with Sumateran orangutans. While is one of the gateways to reach tourist destinations in North Sumatra Province, including the city that has the Maimun City Palace and the Great Mosque that represents the history of the continuity of the Malay Kingdom, the Tjong A Fie House and the colonial colonial buildings that have talked about for years. This study aims to analyze and determine how to encourage tourists, destination images, and tourist satisfaction with tourist loyalty in North Sumatra Province. This research uses quantitative methods with data analysis methods. Multiple linear regression because it is based on two or more independent variables on variables, after that the data processing technique uses SPSS version 22 as a tool. This study found that the results consisted only of motivation variables which did not have a significant effect, while other variables had a significant effect on tourist loyalty. The results showed that the independent variables consisted of motivation variables (X1), destination image variables (X2), and satisfaction (X3) positively and significantly towards the variables supported by tourist loyalty (Y) visiting the tourist area of North Sumatra Province. This study obtained results consisting of the majority of visitors consisting of students aged 17 to 25 years. Lake Toba, Bukit Lawang, and Berastagi are the dominant mainstay sectors, and the level of tourist visits to the Province of North Sumatra is still categorized as low.